BULNER: BUg Localization with word embeddings and NEtwork Regularization - Rodrigues Barbosa, Jacson; Marcondes Marcacini, Ricardo; Britto, Ricardo; Soares, Frederico; Rezende, Solange; M. R. Vincenzi, Auri; E. Delamaro, Márcio (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM), 2019)
Bug localization (BL) from the bug report is the strategic activity of the software maintaining process. Because BL is a costly and tedious activity, BL techniques information retrieval-based and machine learning-based could aid software engineers. We propose a method for BUg Localization with word embeddings and Network Regularization (BULNER). The preliminary results suggest that BULNER has better performance than two state-of-the-art methods.